2016
DOI: 10.2196/jmir.5235
|View full text |Cite
|
Sign up to set email alerts
|

Text Messaging for Exercise Promotion in Older Adults From an Upper-Middle-Income Country: Randomized Controlled Trial

Abstract: BackgroundMobile technology to promote exercise is effective; however, most evidence is from studies of younger groups in high-income countries. Investigating if short message service (SMS) texting can affect exercise participation in older adults from an upper-middle-income country is important considering the proliferation of mobile phones in developing regions and the increased interest of older adults in using mobile phones.ObjectiveThe main objective was to examine the short- and long-term effects of SMS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
166
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(172 citation statements)
references
References 65 publications
(94 reference statements)
3
166
0
3
Order By: Relevance
“…Finally, a recent study examined the impact of a text messaging intervention on increasing exercise among adults 55 to 70 years old [63]. All participants (N=43) received an exercise booklet, and those randomized to the SMS condition received five text messages each week, for 12 weeks.…”
Section: Short Message Service (Sms) or Text Messagingmentioning
confidence: 99%
“…Finally, a recent study examined the impact of a text messaging intervention on increasing exercise among adults 55 to 70 years old [63]. All participants (N=43) received an exercise booklet, and those randomized to the SMS condition received five text messages each week, for 12 weeks.…”
Section: Short Message Service (Sms) or Text Messagingmentioning
confidence: 99%
“…As older adults have more access to cell phones than other technologies and are increasingly using mobile phones and the internet (Anderson & Perrin, 2017;Joe & Demeris, 2013), designing new ways to use these technologies to promote health and physical activity has become an obvious research goal (Gell, Rosenberg, Demiris, LaCroix, & Patel, 2015;O'Reilly & Spruijt-Metz, 2013). Recent studies have shown that texting increases certain domains of self-reported physical activity (Antoine Parker & Ellis, 2016;Kim & Glanz, 2013;Muller, Khoo, & Morris, 2016). For example, Robin et al (2017) showed that guided imagery texts delivered via cell phones were successful at increasing weekly minutes of aerobic physical activity (APA) among older adults, notably by enhancing their motivation.…”
Section: Text Messaging Motivation and Physical Activity In Older Admentioning
confidence: 99%
“…The evidence base for e-& mHealth physical activity and sedentary behavior interventions in older adults is mixed. Some interventions delivered via mobile-phone text messaging (27,28), and the Internet (29)(30)(31)(32)(33) were successful in improving these health behaviors. In contrast, others, delivered via the Internet (34,35), tablet computers (36) and wearable activity trackers (37,38), were not.…”
Section: E-and Mhealth To Impact Physical Activity and Sedentary Behaviormentioning
confidence: 99%